The Role of Affect in the Creation and Intentional Pursuit of Entrepreneurial Ideas - Hayton, James C.; Cholakova, Magdalena (Entrepreneurship Theory and Practice, 2012)
The creation and intentional pursuit of entrepreneurial ideas lies at the core of the domain of entrepreneurship. Recent empirical work in a number of diverse fields such as cognitive psychology, social cognition, neuroscience, and neurophysiology all suggest that dual processes involving affect and cognition have a significant impact on judgment and decision making. Existing cognitive models ignore this significant role. In this article we develop a framework for understanding the role of affect on idea perception and the intention to develop the entrepreneurial idea. We present a set of testable propositions that link affect to entrepreneurial idea perception through its influence on attention, memory, and creativity. A second set of propositions links affect to the intention to pursue these ideas further. We explore the boundary conditions and moderators of the proposed relationships, and discuss the implications of this framework for existing cognitive and psychological perspectives on entrepreneurship.